Radio Frequency Integrated Circuits and Technologies - Ellinger, Frank (Springer Berlin Heidelberg : Imprint: Springer, 2007)
The operation frequencies, bandwidths and data capacities of communications systems are continuously increasing by employing advanced technologies and aggressive scaling of device dimensions. However, the restrictions inherent in scaling make the design of radio frequency integrated circuits a demanding task. To meet the corresponding challenges designers must provide profound skills in several areas including circuit theory, silicon and compound semiconductor technologies, communications standards, system design, measurement techniques, etc. The book aims at addressing all these multidisciplinary issues in a compact and comprehensive form and in a single volume. Suitable for students, engineers and scientists, the manuscript offers the necessary theoretical background together with cookbook-like optimisation strategies and state-of-the-art design examples.